Leisure‐time physical activity and cardiometabolic risk among children and adolescents - Luz M. Cárdenas‐Cárdenas; Ana I. Burguete‐Garcia; Bárbara I. Estrada‐Velasco; Claudia López‐Islas; Jesús Peralta‐Romero; Miguel Cruz; Marcia Galván‐Portillo (Brazilian Society of Pediatrics, 2015)
Objective: To assess the effect of Leisure‐time physical activity (LTPA) on cardiometabolic risk by nutritional status in Mexican children and adolescents. Methods: This was a cross‐sectional study conducted with 1,309 participants aged between 5 and 17 years. Nutritional status was classified according to the BMI Z‐score by age and gender. A previously validated questionnaire was used to evaluate LTPA; a cardiometabolic risk score was calculated. Multiple linear regression analysis was performed to assess the effect of LTPA on cardiometabolic risk. Results: After adjusting for risk factors, mild LTPA were positively associated with cardiometabolic risk score (βMild vs. Intense LTPA: 0.68; 95% CI: 0.18 to 1.18; pfor trend = 0.007). This association became stronger when estimated for overweight (β Mild vs. Intense LTPA: 1.24; 95% CI: 0.24 to 2.24; pfor trend = 0.015) and obese participants (β Mild vs. Intense LTPA: 1.02; 95% CI: 0.07 to 1.97; p for trend = 0.045). Conclusion: Mild LTPA was positively associated with cardiometabolic risk in overweight and obese children and adolescents. Given the emerging childhood obesity epidemic in Mexico, these results may be useful in the design of strategies and programs to increase physical activity levels in order to achieve better health.